Assessing Common Bean Cultivars for Resistance to the Soybean Looper Chrysodeixis includens (Lepidoptera: Noctuidae) - Morando, R. [UNESP]; Baldin, E. L. L. [UNESP]; Cruz, P. L.; Lourencao, A. L. (Entomological Soc Brasil, 2017)
The soybean looper Chrysodeixis includens (Walker) (Lepidoptera: Noctuidae) is known as an important pest of leguminous plants worldwide. In Brazil, this pest species is gaining importance to producers of the common bean Phaseolus vulgaris L. (Fabaceae) because it limits field production of the crop. Chemical control is still the primary method of insect control. However, due to the possible harmful effects of pesticides to humans and the environment, alternative and less aggressive practices are being investigated. For this reason, the use of resistant plant genotypes represents a valuable tool in insect control. This study evaluated the biological aspects of larvae of C. includens confined to 14 bean genotypes under laboratory conditions (26 +/- 2A degrees C; 65 +/- 10% RH; photoperiod of 14 h L:10 h D). The duration of the instars, total duration of the larval phase, consumption while in the larval phase, weight of the fifth instar larvae, larval viability, duration of the pre-pupal and pupal phases, pupal weight, pupal viability, pupal deformity, caterpillar-to-adult cycle, duration of the pre-oviposition and oviposition periods, and total number of viable eggs per female were evaluated. The genotypes IAC Boreal, IAC Harmonia, and IAC Formoso expressed antibiosis, prolonging the caterpillar-to-adult cycle and reducing the larval viability; however, each of these genotypes also experienced high leaf consumption. IAC Jabola expressed moderate levels of antibiosis and/or antixenosis (feeding), while the genotype BRS Horizonte expressed antixenosis (feeding). The data obtained with IAC Boreal, IAC Harmonia, IAC Formoso, IAC Jabola, and BRS Horizonte are promising and may help with the improvement of programs aimed at managing C. includens damage to this leguminous agricultural crop.
Keywords: Host plant resistance; Phaseolus vulgaris L.; antibiosis; antixenosis